Transovarial transmission of mosquito-borne viruses: a systematic review - Janjoter, Sangeeta; Kataria, Divya; Yadav, Mahima; Dahiya, Nisha; Sehrawat, Neelam (Frontiers in Cellular and Infection Microbiology, 2024)
Background A number of mosquito-borne viruses (MBVs), such as dengue virus (DENV), zika virus (ZIKV), chikungunya (CHIKV), West Nile virus (WNV), and yellow fever virus (YFV) exert adverse health impacts on the global population. Aedes aegypti and Aedes albopictus are the prime vectors responsible for the transmission of these viruses. The viruses have acquired a number of routes for successful transmission, including horizontal and vertical transmission. Transovarial transmission is a subset/type of vertical transmission adopted by mosquitoes for the transmission of viruses from females to their offspring through eggs/ovaries. It provides a mechanism for these MBVs to persist and maintain their lineage during adverse climatic conditions of extremely hot and cold temperatures, during the dry season, or in the absence of susceptible vertebrate host when horizontal transmission is not possible. Methods The publications discussed in this systematic review were searched for using the PubMed, Scopus, and Web of Science databases, and websites such as those of the World Health Organization (WHO) and the European Centre for Disease Prevention and Control, using the search terms “transovarial transmission” and “mosquito-borne viruses” from 16 May 2023 to 20 September 2023. Results A total of 2,391 articles were searched, of which 123 were chosen for full text evaluation, and 60 were then included in the study after screening and removing duplicates. Conclusion The present systematic review focuses on understanding the above diseases, their pathogenesis, epidemiology and host–parasite interactions. The factors affecting transovarial transmission, potential implications, mosquito antiviral defense mechanism, and the control strategies for these mosquito-borne viral diseases (MBVDs) are also be included in this review.